GENDER DISTRIBUTION OF PRIMARY SCHOOL TEACHERS IN ZARIA LOCAL EDUCATION AUTHORITY: IMPLICATION FOR EDUCATIONAL PLANNING - Ringim, Musa Saleh; Jumare, Abubakar M. (Sokoto Educational Review, 2017)
This paper attempts to examine the gender distribution of primary school teachers, in Zaria local education authority. The population of the study was one hundred and fifty teachers, the study sampled fifty teachers in the selected primary schools. The opinion of the respondents was tested through a questionnaire. The result was analyzed using a t-test. The findings revealed that most male teachers leave teaching in primary schools because of low salaries, as such female teachers are having high percentage. Also, it was discovered that due to the complexities and nature of women, an academic gap is created in teaching in primary schools. More so, there is an overpopulation of students in classes and an inadequate supply of instructional materials. Finally, it is recommended that the government should increase the funding of primary education and education planners should take note of female complexities while planning for education.